2023
DOI: 10.3389/fevo.2023.1177849
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic change, driving mechanism and spatiotemporal prediction of the normalized vegetation index: a case study from Yunnan Province, China

Abstract: Vegetation indexes have been widely used to qualitatively and quantitatively evaluate vegetation cover and its growth vigor. To further extend the study of vegetation indexes, this paper proposes to study the spatial and temporal distribution characteristics and specific driving mechanisms of vegetation indexes based on the example of Yunnan Province, China, and also adds the study of spatial and temporal prediction methods of vegetation indexes. This paper used data on this region’s normalized vegetation inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Partial correlation analysis can reveal the impact intensity of one factor on another while other factors remain unchanged [11,13]. Multiple correlation analysis can analyze the correlation between two or more factors and a certain factor, so as to identify the comprehensive influences of multiple factors on this factor [50].…”
Section: Correlation Analysis Between Vc Change and Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…Partial correlation analysis can reveal the impact intensity of one factor on another while other factors remain unchanged [11,13]. Multiple correlation analysis can analyze the correlation between two or more factors and a certain factor, so as to identify the comprehensive influences of multiple factors on this factor [50].…”
Section: Correlation Analysis Between Vc Change and Climate Changementioning
confidence: 99%
“…In terms of identifying VC change, researchers mostly adopt linear regression trend analysis [10][11][12][13][14], and a few adopt the ordinary least squares method [15]. At present the, GeoDetector model is one of the most commonly used methods to detect the drivers of vegetation change and has received extensive attention from researchers [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Yan et al (2021) demonstrated that extreme precipitation has remarkable impact on net primary productivity of vegetation and its spatial distribution. Han et al (2023) pointed that relative humidity is the main driving factor of NDVI, compared to other meteorological factors. In the eastern part of the CLLH, vegetation growth is thought to be governed by temperature (Hou et al 2015;Xue et al 2023).…”
Section: Introductionmentioning
confidence: 99%